Al Ghazali's Philosophical Thoughts - Syifa Azzahra; Maspuroh; Rika Rosidah; Santi Rahmawati; Supardi Rusli (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2025)
Philosophy, with its stringent methodology, cultivates critical thinking by encouraging individuals to scrutinize, deliberate, and evaluate the validity and accountability of every idea. Furthermore, its concise concepts render these notions intellectually and scientifically justifiable. As educated Muslims, it is imperative that we comprehend the symbiotic relationship between this philosophical framework and human nature, as ordained by divine decree. This discussion will primarily focus on the philosophical musings of Imam Al-Ghazali, employing a literature study approach that examines his seminal works and related references.